Implementation of temporal lobe contouring protocol in head and neck cancer radiotherapy planning: A quality improvement project. Issue 38 (September 2018) - Ho, Francis; Tey, Jeremy; Chia, David; Soon, Yu Yang; Tan, Chek Wee; Bahiah, Sarahatul; Cheo, Timothy; Tham, Ivan Weng Keong
Abstract : Abstract: Temporal lobe necrosis as result of radiation for nasopharyngeal cancer (NPC) occurs up to 28% of NPC patients. The only effective mitigation is by strict adherence to temporal lobe dose tolerances during radiotherapy planning, which in turn hinges on accurate temporal lobe delineation. We aim to improve the accuracy and to standardize temporal lobe contouring for patients receiving head and neck radiotherapy for NPC in a tertiary teaching hospital in Singapore. The baseline data were obtained from 10 patients in the diagnostic phase and the effect of interventions were measured in 37 patients who underwent head and neck radiotherapy over a 6-month period. We conducted the project based on the Clinical Practice Improvement Program methodology. The baseline pooled mean percentage variation in temporal lobe contouring was 39.9% (0.8%–60.2%). There was a low level of temporal lobe contouring concordance and this provided the impetus for implementation of strategies to improve the accuracy and reproducibility of temporal lobe contouring. The interventions included supervision and training of radiation therapists and residents in temporal lobe contouring, and standardization of temporal lobe contouring with a protocol and contouring atlas. Thirty-seven patients were treated during the study period from June to November 2014. Following implementation of the first set of interventions, the pooled mean percentage variation in temporal lobe contouring decreased but was not sustained. The implementation of the second set of interventions resulted in a decrease from 39.9% (January to September 2014) to 17.3% (October to November 2014) where P = .004 using t test. Weekly variation was seen throughout the study period but the decrease was sustained after standardizing and providing a contouring atlas for temporal lobe contouring. Temporal lobe contouring can be standardized through effective implementation of a temporal lobe contouring protocol and atlas.